THE RELATIONSHIP BETWEEN PERCEIVED WORKPLACE FLEXIBILITY AND WORK-FAMILY FIT IN DUAL CAREER COUPLE IN INDONESIA - Hana Safira; Dewi Syarifah (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Dual career couple is a married couple who both work in a particular agency. In dual career couple, it is known that there is a relationship between perceived workplace flexibility that becomes an individual's assessment about the extent to which an employee feels he has workplace flexibility in completing his work tasks in terms of time (working hours) and his workplace. Certainly this also happened in Indonesia and felt as well as had an influence for several dual career couples